An integrative review on the shadow of abuse in pediatric head trauma - SÖNGÜT, Semra (Universa Medicina, 2025)
Introduction Abusive head trauma (AHT) is a significant public health issue that can lead to severe neurological damage or death in childhood. Often difficult to detect, AHT carries long-term consequences and requires high diagnostic vigilance. This integrative review aims to synthesize the current evidence on abusive head trauma in pediatric patients by identifying distinguishing diagnostic criteria, clinical patterns, and risk factors, in order to support early recognition, accurate diagnosis, and effective intervention strategies by healthcare professionals. Methods This integrative review aimed to systematically include studies published between 2020-2025 and the literature search was conducted in April-June 2025. The databases searched included PubMed and Web of Science. The keywords included in the search were "Abusive head trauma", "child abuse", "non-accidental head injury", "health care professional", "pediatric head trauma". The methodological quality of the included studies was assessed using the Risk of Bias in Non-randomized Studies – of Interventions (ROBINS-I) tool. Results The findings were synthesized under four main themes: diagnostic indicators and differentiation, epidemiological risk factors, short-term clinical outcomes, and long-term developmental effects. Elevated glucose levels (>300 mg/dL), the diagnostic “triad” (subdural hematoma, retinal hemorrhage, and encephalopathy), and increased plasma osteopontin levels were identified as critical diagnostic clues. Additionally, household composition and caregiver characteristics emerged as significant risk factors. Conclusion This integrative review highlights the necessity of identifying high-risk environments and implementing preventive strategies. The evidence presented offers practical, evidence-based insights to support healthcare professionals in accurately diagnosing and managing AHT. It also underscores the need for multidisciplinary prevention efforts and post-trauma monitoring. Ultimately, this study seeks to enhance clinical awareness and improve early identification and intervention strategies for children suffering from abuse-related head trauma.